Identification of Aeromonas Species Isolated from Freshwater Fish with the Microplate Hybridization Method - Sugita, Haruo (1994)
Aeromonas isolates were obtained from the intestinal tracts of six species of cultured freshwater fish and identified on the basis of their genotypic and phenotypic characters. The microplate hybridization method could differentiate type strains of Aeromonas species and related bacteria. DNA-DNA hybridization analysis showed that 65 aeromonad isolates were 72 to 100% related with either Aeromonas caviae, Aeromonas hydrophila, Aeromonas jandaei, Aeromonas sobria, or Aeromonas veronii. As many as 48% of the genotypically identified A. caviae, A. hydrophila, and A. sobria isolates differed from the type strains of corresponding species in one to three phenotypic characters. These results strongly suggest that not all aeromonad isolates from freshwater fish could be identified correctly on the basis of only the phenotypic characters, indicating the usefulness of the microplate hybridization method for the identification of aeromonads.